1999
DOI: 10.1203/00006450-199901000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Antibodies Recognizing Oxidatively Modified Low-Density Lipoprotein in Children

Abstract: The occurrence of circulating antibodies (IgG) against oxidatively modified LDL was investigated in a group of normocholesterolemic, healthy, cardiovascular risk-free children and in a comparable group of normal adults. An increased titer of IgG recognizing Cu++-oxidized or malondialdehyde (MDA)-derivatized LDL (MDA-LDL) was a constant feature in children. The antigenic epitopes recognized by these antibodies were generated rather late in the process of copper-mediated LDL oxidation, concomitantly with the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
0
23
0
2
Order By: Relevance
“…As mentioned previously, the binding activity of anti-oxLDL IgG is significantly higher in children than in adults. 48 These studies seem to support the idea that anti-oxLDL antibodies have a protective function against the development of atherosclerosis and CVD in healthy individuals. Table 3 lists [85][86][87][88][89][90][91][92][93][94] several studies that found negative associations between anti-oxLDL antibodies and CVD and other conditions.…”
Section: Protective Role Of Anti-oxldl Antibodies In Humansmentioning
confidence: 62%
See 2 more Smart Citations
“…As mentioned previously, the binding activity of anti-oxLDL IgG is significantly higher in children than in adults. 48 These studies seem to support the idea that anti-oxLDL antibodies have a protective function against the development of atherosclerosis and CVD in healthy individuals. Table 3 lists [85][86][87][88][89][90][91][92][93][94] several studies that found negative associations between anti-oxLDL antibodies and CVD and other conditions.…”
Section: Protective Role Of Anti-oxldl Antibodies In Humansmentioning
confidence: 62%
“…These antibodies have been found in children, 48 healthy adults, and patients with coronary heart disease. 27 Circulating antibodies recognizing oxLDL are present in cardiovascular risk-free children.…”
Section: Protective Role Of Anti-oxldl Antibodies In Humansmentioning
confidence: 97%
See 1 more Smart Citation
“…4) They display an acute phase response in acutely ill patients, often increasing significantly within hours to days after an event. 5) They may have different influences on atherogenesis, at least in experimental models, in which IgMs, which are more likely to be enriched in natural antibodies present even at birth (26) seem to be atheroprotective, but IgGs seem to be atherogenic, except perhaps in response to vaccination, in which they may be associated with atheroprotection (10,26,34,35,(37)(38)(39). In humans, we have recently shown that IgM OxLDL autoantibodies and IgM apoB-ICs were associated inversely with the presence of angiographically determined CAD, whereas IgG OxLDL autoantibodies and IgG apoB-ICs were positively associated (40).…”
Section: Relationship Of Oxpl/apob Lp(a) and Oxldl Biomarkers To Dementioning
confidence: 97%
“…The finding that PC is a common component of plaque bacteria and that patients with attachment loss have elevated antibody levels against PC therefore argue that the anti-PC response is a common tie between many systemic conditions and periodontal infections. It is also noteworthy that some investigators have reported that anti-oxLDL antibodies are present in newborns and children and increase during childhood (21). It has been speculated that such antibodies may reflect oxidative damage to LDLs; however, a portion of such antibody could reflect exposure to the oral flora during inflammatory episodes.…”
Section: Vol 69 2001mentioning
confidence: 99%